Preparation and characterization of novel film adhesives based on cyanate ester resin for bonding advanced radome. (July 2016) - Wang, Guan; Fu, Gang; Gao, Tangling; Kuang, Hong; Wang, Rongguo; Yang, Fan; Jiao, Weicheng; Hao, Lifeng; Liu, Wenbo
Abstract: In this paper, the novel film adhesives based on phenolphthalein poly(ether sulfone) (PES-C) and epoxy (EP) modified cyanate ester resin (CE) were prepared for bonding an advanced radome. The film adhesives are convenient for applying to manufacture, possessing good adhesion strength, thermal durability and excellent dielectric property. The curing behaviors were confirmed by differential scanning calorimetry (DSC), showing that the main reaction pathways are not varied with adding PES-C but the reaction rates are evidently accelerated, and the film adhesives can be well cured at lower temperature of 177 °C. The adhesion strength was evaluated in lap shear strength and peel strength, indicating that the better adhesion strength is obtained with increasing in PES-C. The maximum value of lap shear strength is 33 MPa at room temperature. The thermal durability was determined by thermal aging tests of lap shear specimens, showing that the decrease in strength gets faster with adding PES-C, and the usability of film adhesives over 2000 h at 200 °C. The dielectric properties were measured by dielectric resonator methods, finding that the introduction of PES-C brings a positive effect on dielectric properties. The lowest value of determined dielectric loss is 0.0075 at 10 GHz.